Chromogranin-A production and fragmentation in patients with Takayasu arteritis - Tombetti, Enrico (Arthritis Res Ther, 2016)
BACKGROUND: Chromogranin-A (CgA) is a secretory protein processed into peptides that regulate angiogenesis and vascular cells activation, migration and proliferation. These processes may influence arterial inflammation and remodelling in Takayasu arteritis (TA). METHODS: Plasma levels of full-length CgA (CgA(439)), CgA fragments lacking the C-terminal region (CgA-FRs) and the N-terminal fragment, CgA(1–76) (vasostatin-1, VS-1) were analysed in 42 patients with TA and 20 healthy age-matched controls. Vascular remodelling was longitudinally assessed by imaging. CgA peptides were related to markers of systemic and local inflammation, disease activity and vascular remodelling. RESULTS: Levels of CgA-FRs and VS-1 were increased in TA. Treatment with proton-pump inhibitors (PPIs) and arterial hypertension partially accounted for CgA levels and high inter-patient variability. CgA(439), CgA-FRs and VS-1 levels did not reflect disease activity or extent. Markers of systemic or local inflammation correlated with higher CgA-FRs and VS-1 in normotensive patients and with higher CgA(439) in hypertensive patients. Treatment with non-biologic anti-rheumatic agents was associated with increased CgA-FRs and a distinctive regulation of CgA processing. Reduced blood levels of anti-angiogenic CgA peptides were associated with vascular remodelling in the groups of patients on PPIs and with arterial hypertension. CONCLUSIONS: The plasma levels of CgA fragments are markedly increased in TA as a consequence of disease- and therapy-related variables. Anti-angiogenic forms of CgA may limit vascular remodelling. Given the effect of the various CgA peptides, it is advisable to limit the therapeutic prescriptions that might influence CgA-derived peptide levels to clearly agreed medical indications until further data become available. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (doi:10.1186/s13075-016-1082-2) contains supplementary material, which is available to authorized users.